2009
DOI: 10.1002/cmdc.200900120
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Property Relationships of a Class of Carbamate‐Based Fatty Acid Amide Hydrolase (FAAH) Inhibitors: Chemical and Biological Stability

Abstract: Cyclohexylcarbamic acid aryl esters are a class of Fatty Acid Amide Hydrolase (FAAH) inhibitors, which includes the reference compound URB597. The reactivity of their carbamate fragment is involved in pharmacological activity and may affect pharmacokinetic and toxicological properties. We conducted in vitro stability experiments in chemical and biological environments to investigate the structure-stability relationships in this class of compounds. The results show that electrophilicity of the carbamate influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 57 publications
0
31
0
Order By: Relevance
“…URB694) belongs to a recently reported second generation of phenyl carbamate FAAH inhibitors with improved pharmacological characteristics, including higher brain penetration. [20,28] To demonstrate the utility of our method we synthesized [ 11 C]-16 in quantities and qualities suitable for animal imaging studies (Scheme 1). The position of the radiolabel at the carbonyl carbon is crucial for tagging FAAH with this class of inhibitor as this is the point of attachment to the enzyme with loss of the O-biaryl group.…”
Section: Resultsmentioning
confidence: 99%
“…URB694) belongs to a recently reported second generation of phenyl carbamate FAAH inhibitors with improved pharmacological characteristics, including higher brain penetration. [20,28] To demonstrate the utility of our method we synthesized [ 11 C]-16 in quantities and qualities suitable for animal imaging studies (Scheme 1). The position of the radiolabel at the carbonyl carbon is crucial for tagging FAAH with this class of inhibitor as this is the point of attachment to the enzyme with loss of the O-biaryl group.…”
Section: Resultsmentioning
confidence: 99%
“…Among such inhibitors are various alkyl-and aryl-carbamates and ureas responsible for the mechanism-based inhibition of enzymes by formation of carbamyl enzymes. Among these enzymes are fatty acid amide hydrolase (34,42), monoacylglycerol lipase (25), acetyl cholinesterase (21), and Pseudomonas species lipase (22). In all of these cases the enzyme forms a covalent carbamyl enzyme via the active-site serine, including in some cases via a substituted piperidine carbamyl link (25) as is the case with NXL104.…”
Section: Vol 54 2010 Inactivation Of ␤-Lactamases By Nxl104 5135mentioning
confidence: 99%
“…12 Structure-activity relationship (SAR) studies showed that conjugated, electron-donor groups on the biphenyl scaffold of URB524 (which increase electron density around the carbamate carbon) are associated with enhanced carbamate stability both in alkaline buffer and in rat plasma. 13 Conversely, these groups do not affect FAAH inhibitor potency in vitro. 7 To understand this apparent discrepancy, we here apply a QM/MM approach to model the carbamoylation reaction of FAAH by the reference inhibitor URB524 (IC 50 = 25.6 nM) and by its p-OH (URB694, IC 50 = 30.0 nM) and p-NH 2 (URB618, IC 50 = 27.2 nM) derivatives (Fig.…”
mentioning
confidence: 99%